Cytotoxic Activity of Dialium Guineense Wild (Fabaceae) Fruit and Stem Bark Methanol Extracts and Fractions (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Cancer is a disease characterized by uncontrollable multiplication and spread of abnormal forms of the body’s own cells. Due to the challenges of orthodox drugs other treatment options are being investigated. Dialium guineense has found ethnomedicinal application in the management of various ailments including cancer.Objectives: To evaluate the cytotoxic activity of D. guineense fruit and stem bark extracts using preliminary and confirmatory methods.Material and method: Preliminary screening was carried out on the extracts using bench-top assay methods for cytotoxicity involving the use of tadpoles of Raniceps ranninus (20-200 µg/mL) and growth inhibition with radicle of Sorghum bicolor seeds (1-30 mg/mL). The extracts were further tested on a breast cancer cell line (AU 565) at 50 μg/mL using 3-(4, 5- dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. Solvent partitioning of the stem bark extract was carried out using chloroform and the resulting fractions subjected to biological testing.Results: The stem bark extract showed 100 % mortality at 40 µg/mL in the tadpole lethality assay while the fruit showed no mortality. The aqueous fraction of the stem bark extract was also more active than the chloroform fraction with an LC50 of 32.4 μg/mL. A concentration dependent effect was observed in the growth inhibitory test using S. bicolor with 67.92 and 49.06 % reductions obtained for the stem bark and fruit extracts respectively. The chloroform fraction produced the highest anticancer effect with 46.55 % inhibition against AU 565 cell line.Conclusion: D. guineense stem bark has cytotoxic potential and is a good candidate for further in vivo anticancer studies.